2015
DOI: 10.1002/chem.201406305
|View full text |Cite
|
Sign up to set email alerts
|

Pd0‐Catalyzed Intramolecular α‐Arylation of Sulfones: Domino Reactions in the Synthesis of Functionalized Tetrahydroisoquinolines

Abstract: A new strategy for the synthesis of tetrahydroisoquinolines based on the Pd(0)-catalyzed intramolecular α-arylation of sulfones is reported. The combination of this Pd-catalyzed reaction with intermolecular Michael and aza-Michael reactions allows the development of two- and three-step domino processes to synthesize diversely functionalized scaffolds from readily available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…During the optimization of the domino process leading to tetrahydroisoquinolines, 12 we realized that the most challenging step of the sequence was the sulfone α-arylation reaction. 21 So, before embarking on the development of a domino process to access 3-substituted indoles, we first examined the palladium-catalyzed α-arylation of β-(2-iodoanilino) sulfones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the optimization of the domino process leading to tetrahydroisoquinolines, 12 we realized that the most challenging step of the sequence was the sulfone α-arylation reaction. 21 So, before embarking on the development of a domino process to access 3-substituted indoles, we first examined the palladium-catalyzed α-arylation of β-(2-iodoanilino) sulfones.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of 1a with the Pd 2 (dba) 3 /xantphos couple as the precatalyst and K 3 PO 4 as the base in DMF, an effective combination for the domino sequence starting from closely related 2-iodobenzylamines, 12 resulted in the decomposition of the starting material (entry 1, Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solé and co-workers reported a domino four-step aza-Michael/α-arylation/Michael addition/β-elimination strategy to achieve 3-[2-(phenylsulfonyl)ethyl]indoles (Scheme 29) [54]. From the results of a previous similar synthesis of tetrahydroisoquinolines [55], the authors knew that, conversely from acrylates, the competitive Heck reaction did not interfere with the initial aza-Michael addition and that the sulfone α-arylation was the most important step to be optimized. Then, the authors found that the higher electrophilicity and the higher acidity of phenyl sulfone allowed recovering of higher yields than methyl sulfone.…”
Section: Palladiummentioning
confidence: 99%
“…In recent years, different domino processes combining palladium‐catalyzed transformations with Michael addition reactions have been developed for the synthesis of a variety of aza‐heterocycles . In this context, we have recently reported the efficient synthesis of highly functionalized tetrahydroisoquinolines and indoles by domino aza‐Michael/Pd‐catalyzed α‐arylation/Michael addition processes based on the use of sulfones both as electrophiles and nucleophiles. To further generalize the application of these synthetic methodologies and access diversely functionalized heterocycles, we were interested in exploring the feasibility of other electron‐withdrawing groups in the domino α‐arylation/Michael addition strategy.…”
Section: Introductionmentioning
confidence: 99%